Polyethylene terephthalate (PET) recycling: A review - Tomy Muringayil Joseph; Seitkhan Azat; Zahed Ahmadi; Omid Moini Jazani; Amin Esmaeili; Ehsan Kianfar; Józef Haponiuk; Sabu Thomas (Case Studies in Chemical and Environmental Engineering, 2024)
It is difficult to reuse wastes from polymers due to the mismatch between the amount of contaminants and the secondary polymers and the quality of the feed. This type of operation is much more expensive and cost-effective than the production of polymer raw materials from the latest materials. However, the reuse of recyclable polymers is beneficial if used extensively in the production of various concrete products and wood-polymer boards. This is done only if cleaning and sorting are not particularly important for the production of polymer products. Polyethylene terephthalate (PET) is a widely used polymer in various industries due to its excellent physical and chemical properties. Besides, the increasing use of PET products has led to a global crisis in waste management, as improper disposal of products has caused significant environmental damage. PET is a major source of accumulated waste in landfills, and to address this issue, recycling methods have evolved. In this regard, the present review examines various techniques involved in the recycling of PET. Conventional recycling methods and the influence of diverse depolymerization reaction variables were discussed, and the upsides and downsides of each technique were considered. The review summarizes major advances in recycling technologies for plastic waste, focusing on the bio-recycling of PET, aiming for sustainable, economical solutions in the circular economy.